Correlation Of Neutrophil Lymphocyte Ratio And Platelet Lymphocyte Ratio With Severity Of COVID-19 - Warman, Fadil Ahmadhia; Yulia, Dwi; Kadri, Husnil; Mulyana, Roza; Yusri, Elfira; Putra, Syandrez Prima (Majalah Kedokteran Andalas, 2025)
The neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR) tests are simple tests can be done before a COVID-19 patient hospitalized. This examination is useful for determining the diagnosis and prognostic of the patient. The aim of the study was to determine the correlation between NLR and PLR with the severity of COVID-19. This research was an analytical study with a cross-sectional approach using secondary data from 289 medical records of patients with confirmed COVID-19 for the period June-August 2021. The total sampling technique was used and processed with the chi-square test. Most of the research subjects were in the range of 26-45 years (28.4%). More than half of the subjects were female (61.6%). There were 99 patients (34.3%) with severe conditions. Less than half of the patients had abnormal leukocyte and platelet examination results, namely 64 (22.1%) and 56 (19.4%). Patients with abnormal NLR and PLR examinations were 135 (46.7%) and 123 (42.6%). There was a significant correlation between NLR and the severity of COVID-19 inpatients (p<0.001, OR=9.452). There is a significant correlation between PLR and the severity of COVID-19 inpatients (p<0.001, OR=7.268).Â This study concludes a significant correlation between NLR and PLR with the severity of COVID-19.